Living with Bipolar Disorder : a Guide for Individuals and Families (Updated Edition). - Otto, Michael W. (Oxford University Press, USA, 2011)
Living with Bipolar Disorder is designed to help patients and their families develop the skills they need to be good consumers of treatment and to become expert partners in the management of this challenging disorder. Drawing on research documenting the strength of combining drug treatments with behavioral interventions for fighting bipolar disorder, the authors of this book take a skill-based, family-and-friends approach to managing the ups and downs commonly experienced with bipolar disorder. Readers will learn how to better recognize mood shifts before they happen, minimize their impact, an.